Mengenal dan Menemukan Diri melalui Kebersamaan dengan Orang Lain - Tirtawinata, Christofora Megawati (Bina Nusantara University, 2013)
Each individual needs to know her/himself well because self-knowing is the gateway to success. By using a variety of ways to get to know oneself, such as by psychological test and personality test an individual can find her/himself. In addition, humans are social beings that cannot be separated from other human beings. Therefore, individuals can find her/himself and toward perfection through solidarity with others and practicing the concept of Johari Window. Article was prepared by using the method of observation and study of literature.